Genomic characterization of a multidrug-resistant Staphylococcus xylosus from Ecuadorian open market avocados: food safety and public health implications - Tenea, Gabriela N.; Angamarca, Evelyn (Frontiers in Microbiology, 2025)
IntroductionFoodborne bacterial infections remain a critical global health challenge, exacerbated by the increasing prevalence of antimicrobial resistance (AMR). Misuse of antimicrobials in agriculture and inadequate food handling practices facilitate the spread of resistant bacteria across the human–animal–environment interface, a central concern of the One Health approach. Comprehensive understanding of microbial threats in food systems is vital for effective risk assessment and control. In this study, we report the first complete genome of a multidrug-resistant Staphylococcus xylosus strain, FFCShyA4, isolated from commercially sold avocados.MethodsWhole-genome sequencing and comparative genomics were employed for taxonomic classification and phylogenetic analysis. In silico tools identified antibiotic resistance genes (ARGs), virulence factors, mobile genetic elements (MGEs), CRISPR loci, genomic islands, and biosynthetic gene clusters (BGCs). In vitro assays assessed hemolysis, gelatinase activity, antibiotic susceptibility, and PCR-based gene detection.ResultsThe FFCShyA4 genome spans 3.09 Mb with a 32.63% GC content and includes a 32 kb plasmid. It shares 99.97% average nucleotide identity with S. xylosus NBRC 109770 yet displays extensive structural rearrangements indicative of niche-specific adaptation. The genome encodes 2,720 protein-coding genes, including ARGs for β-lactams, macrolides, fluoroquinolones, tetracyclines, and lincosamides. The presence of 133 MGEs, CRISPR systems, an intact prophage, and 138 genomic islands reflects a strong potential for horizontal gene transfer. Virulence profiling identified 121 genes across 34 families, with a predicted human pathogenicity of 98.2%. BGCs linked to bacteriocins, siderophores, and staphylopine biosynthesis were also detected. In vitro assays confirmed multidrug resistance and pathogenicity.ConclusionThese results emphasize the critical need for integrated One Health surveillance of antimicrobial resistance within food production and commercial environments to facilitate early detection and reduce dissemination of resistance determinants across interconnected human, animal, and environmental reservoirs.